Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to prove $\exp(x+y) = \exp(x) \exp(y)$.

I may use that $$\exp(x) = \sum_{n=0}^\infty \frac {x^n}{n!}$$ I further know how to multiply two power series in one point, i.e. if $f(x) = \sum_{n=0}^\infty c_n(x-a)^n$ and $g(x) = \sum_{k=0}^\infty d_n(x-a)^n$ then $$ f(x)g(x) = \sum_{n=0}^\infty e_n(x-a)^n $$ with $$ e_n = \sum_{m=0}^n c_md_{n-m} $$

share|cite|improve this question
What's the question? – nbubis Jan 23 '13 at 18:54
Presumably you tried to multiply the power series for $\exp(x)$ and $\exp(y)$. What did you get stuck on? – rschwieb Jan 23 '13 at 18:54
The title is the question @nbubis. This question is from Tao Analysis II and he gives the hint with the multiplication of power series. I dont see how to apply that hint. – Epsilon Jan 23 '13 at 18:57
Ok I got it :) Can I delete this question ? – Epsilon Jan 23 '13 at 19:00
This must be a duplicate... – Fabian Jan 23 '13 at 19:02
up vote 11 down vote accepted

\begin{align} \exp(x+y)&=\sum_n\frac{(x+y)^n}{n!} \\\\ &=\sum_{n}\frac{1}{n!}\sum_{a+b=n} {n \choose a} x^ay^b \\\\ &= \sum_{n}\frac{n!}{n!}\sum_{a+b=n}\frac{x^a}{a!}\frac{y^b}{b!} \\\\ &= \sum_{a,b} \frac{x^a}{a!}\frac{y^b}{b!} \\\\ &= \exp(x)\cdot\exp(y) \end{align}

share|cite|improve this answer
You can write faster than me :D – Epsilon Jan 23 '13 at 19:16
You overcomplicated things in your solution. There is no need to work with a generating function as you have done. Also, you left out some steps in your first equality when going from a product of two generating functions into a single generating function. – pre-kidney Jan 23 '13 at 19:17
I gave the legitimation for that in my question. – Epsilon Jan 23 '13 at 19:19
Oh, I see now. Thanks for pointing that out :) – pre-kidney Jan 23 '13 at 19:20
you have used this equality: $$\bigsqcup _n\{(a,b) \mid a+b=n\}=\{(a,b)\mid \}$$ and absolute convergence. – user59671 May 9 '13 at 11:05

My solution

Let $x,y \in \mathbb R$ and

$f(z) := \sum_{n=0}^\infty \left(\frac {x^n}{n!} \right )z^n$ and $g(z) := \sum_{n=0}^\infty \left(\frac {y^n}{n!} \right )z^n$. Then $\exp(x) \exp(y) = f(1)g(1)$. That is $$ f(z)g(z) = \sum_{n=0}^\infty \left( \sum_{k=0}^m \frac {x^m y^{n-m}}{m! (n-m)!} \right)z^n $$ $$ = \sum_{n=0}^\infty \frac 1 {n!} (x+y)^n z^n $$ thus $f(1)g(1) = \exp(x+y)$.

share|cite|improve this answer

This can actually be done without writing a single sum. Consider the function $$ f(x, y) = \frac{e^x e^y}{e^{x+y}}. $$ Observe that $$ \frac{\partial f}{\partial x} = \frac{e^x e^y e^{x+y} - e^x e^y e^{x+y}}{(e^{x+y})^2} = 0. $$ Similarly, $$ \frac{\partial f}{\partial y} = \frac{e^x e^y e^{x+y} - e^x e^y e^{x+y}}{(e^{x+y})^2} = 0. $$ This shows that $f$ is a constant function. Now, we need only to use the series definition to show $f(0, 0) = 1$. Then, by rearrangement, we have the desired result: $$ e^{x+y} = e^x e^y. $$

share|cite|improve this answer
Thanks for this one – JacksonFitzsimmons Jul 15 '15 at 21:50

$A(t)=\exp(x) = \sum_{n=0}^\infty \frac {x^n}{n!}t^n$
$B(t)=\exp(y) = \sum_{n=0}^\infty \frac {y^n}{n!}t^n$
$C(t) = A(t)*B(t)=\sum_{n=0}^\infty (\sum_{k+z=n}^\ \frac {x^k}{k!}*\frac {y^z}{z!})t^n=\sum_{n=0}^\infty \frac {(x+y)^n}{n!}t^n=exp(x+y)$

and use $t=1$

sry i was too late^^

share|cite|improve this answer
Duplicate of the two answers ^^ – Epsilon Jan 23 '13 at 19:23
Actually, both you and @nordmann use an extraneous generating function [in the variables $t$,$z$ respectively]. The reason why I say "extraneous" is because if you look at my solution above, no new variable need be introduced. – pre-kidney Jan 23 '13 at 19:43
sry im new to this latex stuff^^ – nordmann Jan 23 '13 at 23:16

Euler formula says that (exponential form of a complex number) $$e^{i\theta}=\cos\theta+i\sin\theta.$$ Therefor $$e^{x+y}=\cos(-i(x+y))+i\sin(-i(x+y))\\=\cos(xi+yi)-i\sin(xi+yi)\\=(\cos ix\cos iy-\sin ix\sin iy)+i(\sin ix\cos iy+\cos ix\sin iy)\\=(\cos ix+i\sin iy)(\cos iy+i\sin iy)\\=e^xe^y.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.